A Highly Abundant Lectin Protein in Arabidopsis thaliana Confers Resistance Against Pathogens - Omega, Maria prihtamala; Hall, Skye Thomas; Schenk, Peer; Kobe, Bostjan (ANNALES BOGORIENSES, 2008)
Lectins are glycoproteins that recognize and bindÂ  to specific carbohydrates. they areÂ  involvedÂ  in a range of biologicalÂ  functions,Â  suchÂ  asÂ  plant defence,Â  storageÂ  proteinsÂ  seedÂ  germinationÂ  andÂ  plantÂ  microbeÂ  interactions. Lectin 3.1Â  (At3g 15356) is a protein in plant model , Arabidopsis thaliana, that has been shownÂ  to be up-regulated inÂ  allÂ  defenceÂ  pathways, especiallyÂ  inÂ  responceÂ  to methylÂ  ester jasmonateÂ  (MJ) . AllÂ  thal wasÂ  knownÂ  aboutÂ  the geneÂ  wasÂ  thatÂ  itÂ  hadÂ  goodÂ  homologyÂ  toÂ  theÂ  beta domainÂ  of legumeÂ  lectins. That aim ofÂ  thisÂ  project wasÂ  to characterizeÂ  theÂ  structureÂ  andÂ  functionÂ  ofÂ  theÂ  IectinÂ  proteinÂ  usingÂ  CD spectra andÂ  X-rayÂ  crystallography. AÂ  TÂDNAÂ  insertionÂ  lineÂ  for theÂ  lectinÂ  geneÂ  andÂ  a number Â of 35SÂ  over-expressionÂ  linesÂ  thatÂ  hadÂ  varyingÂ  levelsÂ  of expression had been generated, but none of these showed any obviousÂ  phenotype. Two protein bands were observed onÂ  Comassie stained SDS-PAGE gelsÂ  inÂ  the over-expressionÂ  lines andÂ  in MJÂ  induced wild-typeÂ  (WT) . TheÂ  two protein bands representedÂ  twoÂ  isoforms ofÂ  theÂ  lectin 3.1Â  protein ; inÂ  a glycsylation assay theÂ  larger proteinÂ  band was shownÂ  to be heavily glycosylated . A nematode (M. incognita) disease assay djscoveredÂ  that theÂ  lectin over-expression linesÂ  hadÂ  lessÂ  nematodeÂ  eggsÂ  comparedÂ  toÂ  thatÂ  of the WT andÂ  thatÂ  theÂ  insertionÂ  lineÂ  hadÂ  more nematodeÂ  eggs Â thanÂ  the WT. ThisÂ  dataÂ  providesÂ  evidenceÂ  that Â Â lectinÂ  3. 1Â  improves. plantÂ  resistanceÂ  against M. incognita infection.Â  interestingly,Â  the nematode gutÂ  liningÂ  containsÂ  fucose withÂ  whichÂ  IectinÂ  3.1 bindsÂ  to.Â Keywords: ArabidopsisÂ  thaliana,Â  lectinâs structure andÂ  function, Â pathogen resistance